Identification and Preliminary Functional Analysis of Responsive Genes to Short-term Heat Stress in Lettuce - Shuping He; Guotao Huo; Guojun Ge; Li Du; Du Long; Lijun Luo; Ping Long; Shiwei Wei (Journal of the American Society for Horticultural Science)
Lettuce is a commonly consumed vegetable worldwide, due to its crisp edible organs and rich nutrition. Heat stress is known to seriously threaten its growth and development. However, research on lettuce response to heat stress focusing on molecular aspects is limited. Therefore, we aimed to understand the complex molecular mechanisms underlying the regulation of lettuce plant response to heat stress (37 °C), by transcriptomic analysis of a heat-resistant lettuce variety (K482) following heat stress treatment for 1.5 and 3 days. A total of 3798 and 4121 differentially expressed genes (DEGs) were identified at 1.5 and 3 days vs. the control after heat treatment, respectively; they were mostly enriched in protein processing in the systemic lupus erythematosus, alcoholism, neurotrophin signaling pathways, and the cell cycle. Most DEGs were NACs, HSPs, MYBs, bHLHs, and WRKYs. Transcriptome analysis showed that the NAC domain transcription factor LsNAC28, which is associated with heat response, is up-regulated during heat stress and LsNAC28 inhibited yeast growth under heat stress (37 °C). These findings provide a basis to comprehensively understand the complex molecular mechanism of lettuce response to heat stress.